N-Sulfation of Heparan Sulfate Regulates Early Branching Events in the Developing Mammary Gland - Bush, Kevin T. (American Society for Biochemistry and Molecular Biology, 2012)
Branching morphogenesis, a fundamental process in the development of epithelial organs (e.g. breast, kidney, lung, salivary gland, prostate, pancreas), is in part dependent on sulfation of heparan sulfate proteoglycans. Proper sulfation is mediated by biosynthetic enzymes, including exostosin-2 (Ext2), N-deacetylase/N-sulfotransferases and heparan sulfate O-sulfotransferases. Recent conditional knockouts indicate that whereas primary branching is dependent on heparan sulfate, other stages are dependent upon selective addition of N-sulfate and/or 2-O sulfation (Crawford, B .E., Garner, O. B., Bishop, J. R., Zhang, D. Y., Bush, K. T., Nigam, S. K., and Esko, J. D. (2010) PLoS One 5, e10691; Garner, O .B., Bush, K. T., Nigam, S .K., Yamaguchi, Y., Xu, D., Esko, J. D., and Nigam, S. K. (2011) Dev. Biol. 355, 394–403). Here, we analyzed the effect of deleting both Ndst2 and Ndst1. Whereas deletion of Ndst1 has no major effect on primary or secondary branching, deletion of Ndst2 appears to result in a mild increase in branching. When both genes were deleted, ductal growth was variably diminished (likely due to variable Cre-recombinase activity), but an overabundance of branched structures was evident irrespective of the extent of gland growth or postnatal age. “Hyperbranching” is an unusual phenotype. The effects on N-sulfation and growth factor binding were confirmed biochemically. The results indicate that N-sulfation or a factor requiring N-sulfation regulates primary and secondary branching events in the developing mammary gland. Together with previous work, the data indicate that different stages of ductal branching and lobuloalveolar formation are regulated by distinct sets of heparan sulfate biosynthetic enzymes in an appropriate growth factor context.